Tinjauan Yuridis dan Praktik Bisnis terhadap Perlindungan Konsumen dalam Transaksi E-Commerce di Indonesia (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The rapid growth of e-commerce transactions in Indonesia brings convenience to consumers, but also raises serious challenges in terms of legal protection of consumer rights. This study aims to assess the effectiveness of the applicable legal framework, examine the business practices of e-commerce actors, and formulate strategies to strengthen consumer protection in the digital realm. This study is important considering the gap between the prevailing regulations and the dynamics of the field and the low awareness of consumers of their rights in electronic transactions. This research uses a normative juridical method with a qualitative approach. Primary data is obtained from a literature study of national laws and regulations such as Law Number 8 of 1999 concerning Consumer Protection and Law Number 11 of 2008 concerning Electronic Information and Transactions and its amendments. Secondary data is obtained through a review of relevant scientific journals, institutional reports, and previous research results. The analysis is conducted descriptively-analytically by examining the synchronization between existing legal norms and their implementation in e-commerce business practices in Indonesia. The results show that although the legal framework for consumer protection in Indonesia is textually adequate, its implementation in practice still encounters obstacles, including weak supervision, lack of effectiveness of consumer complaint mechanisms, and limited consumer understanding of their rights. Business practices in the e-commerce sector also often do not fully implement the principles of honesty, transparency, and accountability, especially in terms of returning goods, guaranteeing product quality, and protecting personal data. Therefore, a strategy to strengthen consumer protection is needed, including regulatory reform, strengthening digital supervision, consumer education, and increasing synergy between the government, business actors, and consumer protection institutions. This research emphasizes the urgency of establishing a consumer protection system that is responsive to technological changes and digital transaction patterns, in order to create a healthy, equitable, and consumer satisfaction and safety-oriented e-commerce climate.